Three-Dımensıonal Anımatıon-Based Rubık's Cube Algorıthm Tutorıal Vıdeo Wıth Mdlc Method - Bayu Syahputra; Jimmy Pratama; Steven Marlin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Society often identify rubik’s cube as a “game for smart people” because it seems too complex and the needing to remember the algorithm just like remembering math equations so people don’t want to try playing rubik’s cube. To attract someone’s interest in learning rubik’s algorithm, we need a media that is easy to understand and easy steps to follow by showing both visual and audio. Tutorial video of rubik’s algorithm based in three dimentional character can portrait the real scrambled cube and every algorithm is shown so everyone that watch the video can follow it easily and also sharpen thinking skill. Tutorial video of rubik’s algorithm based in three dimentional character is made by using MDLC method that stands for Multimedia Development Cycle that consist of 6 elemens which is concept, design, material collecting, assembly, testing, and distribution. There are several independent variables that can affect students in showing interest in studying which is : Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Learning Value, and Hedonic Motivation also students interest that will be marked as dependent variable that will be refered as Behavior Intention. Based on the analitic result, independent variables that affects positively to dependent variable are Performance Expectancy, Effort Expectancy, Social Influence, meanwhile Facilitating Conditions, Learning Value, and Hedonic Motivation affects negatively to Behavior Intention.